Fresh properties of self-consolidating concrete incorporating palm oil fuel ash as a supplementary cementing material - Safiuddin, M.; Md. Isa, M.H.; Jumaat, Mohd Zamin (Chiang Mai Journal of Science, 2011)
This paper reports the key fresh properties of self-consolidating concrete (SCC) incorporating palm oil fuel ash (POFA) as a supplementary cementing material. Various SCC mixtures were produced based on the water/binder ratio of 0.50 and 0.60. POFA was incorporated in concretes substituting 0, 5, 10, and 15 of cement by weight. The fresh concretes were tested for the key workability properties of SCC such as filling ability, passing ability, and segregation resistance. The filling ability was determined with respect to slump flow, T 50cm spread time, and V-funnel flow time. The passing ability was measured with regard to J-ring flow. The segregation resistance was qualitatively assessed in respect of visual stability index. The segregation resistance was also quantified by sieve and column tests. Test results showed that the slump flow and J-ring flow decreased whereas the T 50cm spread time and V-funnel flow time increased with higher POFA content. The presence of POFA improved the stability of concrete mixture and provided a lower visual stability index. In addition, the segregation index and segregation factor obtained from sieve and column tests, respectively, decreased with greater POFA content. The overall findings suggest that the filling ability and passing ability of SCC decreased whereas its segregation resistance increased with higher POFA content.